The (Re)Construction of Identities in Popular Andean Music in Peru: A Field of Cultural Dispute and Negotiation - Pineau, Fanny (2011)
This paper analyzes the construction and transformation of the cultural identities in Peru: a complex, multidimensional, conflicting, and dynamic process in  which local, national, global, polítical, and historical referents that involve individual and collective subjects fight for hegemony. The Andes regional folk music is one of the scenarios that offer the biggest and richest elements in cultural identity studies.